Zir b. Hubaysh and Hadith Narration - Taş, Mustafa (Dicle University, 2025)
The Sahâba and tabiûn have an important place in the transmission of hadith and sunnah. The muhadramûn, who are among these two strata, have also made important efforts in this regard. In this study, the hadiths narrated by Zir b. Hubaysh (d. 82/701), one of the muhadramûn and an important figure in Qiraah and hadith, was investigated, and his role in the transmission of hadith and sunnah was attempted to be determined. In this way, the subjects on which he narrated hadith, his areas of interest and what he paid more attention to were revealed. Collecting the hadiths narrated by the narrators, making their transmission (tahric) and categorising them under headings according to their subjects are among the important issues that need to be addressed in the science of hadith. With this study, it has been determined that Zir b. Hubaysh has narrations on subjects such as Qiraat and Tafsir, which are his special fields of interest, as well as ibadah such as ablution, prayer, fasting, and subjects such as knowledge, fiten, and fazil. This study will also reveal the narrations of Imam ‘Asim (d. 127/745), our imam of Qiraat, who narrated the hadith from Zir b. Hubaysh.

Sahâbe ve tabiûnun hadis ve sünnetin naklinde mühim bir yeri vardır. Bu iki tabaka arasında yer alan muhadramûnun da bu konuda önemli gayretleri olmuştur. Bu çalışmada muhadramûndan olup kıraat ve hadis ilminde önemli bir şahsiyet olan Zir b. Hubeyş’in (ö. 82/701) rivayet ettiği hadisler araştırılarak hadis ve sünnetin naklindeki yeri tespit edilmeye çalışılmıştır. Bu bağlamda Zir b. Hubeyş’in hangi konularda hadis rivayet ettiği, ilgi alanları ve daha çok nelere dikkat ettiği ortaya konulmuştur. Râvilerin rivayet ettiği hadislerin toplanması, tahriclerinin yapılması ve başlıklar altında konularına göre kategorize edilmesi hadis ilminde araştırılması gereken mühim konular arasında yer almaktadır. Yapılan bu çalışma ile Zir b. Hubeyş’in özel ilgisi olan kıraat ve tefsir alanlarında rivayetleri olduğu gibi abdest, namaz, oruç gibi ibadetler ile ilim, fiten ve fezâil gibi konularda da rivayetlerinin olduğu tespit edilmiştir. Bu çalışmada ayrıca Zir b. Hubeyş’ten hadis rivayet eden kıraat imamımız İmam Âsım’ın da (ö. 127/745) rivayetleri böylece ortaya çıkmış olmaktadır.
Zir b. Hubeyş ve Hadis Rivayeti
Keywords: Hadith; Hadis